Fault tolerant detection and tracking of multiple sources in WSNs using binary data - Laoudias, Christos; Panayiotou, Christos G.; Michaelides, Michalis P. (My University, 2009)
This paper investigates the use of a Wireless Sensor Network for detecting and tracking the location of multiple event sources (targets) using only binary data. Due to the simple nature of the sensor nodes, sensing can be tampered (accidentally or maliciously), resulting in a significant number of sensor nodes reporting erroneous observations. Therefore, it is essential that any event tracking algorithm used in Wireless Sensor Networks (WSNs) exhibits fault tolerant behavior in order to tolerate misbehaving nodes. The main contribution of this paper is the development of a simple and decentralized algorithm that uses the binary observations of the sensors for tracking multiple targets in a fault-tolerant way. Furthermore, tracking is performed in real-time by the alarmed sensor nodes that are elected as leaders, utilizing only information from their neighbors. ©2009 IEEE.
Keywords: Fault tolerance; Fault detection; Wireless sensor networks; Target tracking; Event detection; Electrical fault detection; Fault location; Intelligent sensors; Computer networks; Pollution measurement